Molecular and Antimicrobial Susceptibility Characterization of Escherichia coli Isolates from Bovine Slaughterhouse Process - José Vázquez-Villanueva; Karina Vázquez; Ana Verónica Martínez-Vázquez; Alfredo Wong-González; Jesus Hernández-Escareño; Omar Cabrero-Martínez; Wendy Lizeth Cruz-Pulido; Abraham Guerrero; Gildardo Rivera; Virgilio Bocanegra-García (Antibiotics, 2023)
Antimicrobials are routinely used in human and veterinary medicine. With repeated exposure, antimicrobials promote antibiotic resistance, which poses a threat to public health. In this study, we aimed to determine the susceptibility patterns, virulence factors, and phylogroups of E. coli isolates during the killing process in a bovine slaughterhouse. We analyzed 336 samples (from water, surfaces, carcasses, and feces), and 83.3% (280/336) were positive for E. coli. The most common phenotypic resistances that we detected were 50.7% (142/280) for tetracycline, 44.2% (124/280) for cephalothin, 34.6% (97/280) for streptomycin, and 36.7% (103/280) for ampicillin. A total of 82.4% of the isolates had resistance for at least one antimicrobial, and 37.5% presented multiresistance. We detected a total of 69 different phenotypic resistance patterns. We detected six other resistance-related genes, the most prevalent being tetA (22.5%) and strB (15.7%). The prevalence values of the virulence genes were 5.4% in hlyA, 1.4% in stx1, and 0.7% in stx2. The frequencies of the pathogenic strains (B2 and D) were 32.8% (92/280) and 67.1% (188/280) as commensals A and B1, respectively. E. coli isolates with pathogenic potential and multiresistance may represent an important source of dissemination and a risk to consumers.